Activation of Opioid Receptors Attenuates Ischemia/Reperfusion Injury in Skeletal Muscle Induced by Tourniquet Placement - Yue-Xian Guo; Gui-Ying Wang; Wen-jie Cheng; Cai-Zhen Yan; Shuang Zhao; Zhao Li; Peng Liu; Xiu-Li Wang (Mediators of Inflammation)
Background and Objectives. Tourniquet-induced ischemia/reperfusion (I/R) injury is a common clinical problem for patients receiving surgery. The objective of this study is to determine if oxycodone (Oxy) reduces skeletal muscle I/R damage induced by tourniquet placement and explores the underlying mechanisms. Method. Mice were randomly assigned to the sham, I/R, Oxy, and I/R with Oxy groups. Oxy was injected intraperitoneally 30 min before tourniquet placement. Morphological changes of the gastrocnemius muscle in these mice were assessed by hematoxylin-eosin (HE) staining and electron microscopy. Expression levels of TLR4, NF-κB, SIRT1, and PGC-1α in the skeletal muscles were detected by western blot. Blood TNF-α levels, gastrocnemius muscle contractile force, and ATP concentration were examined. Results. Compared with the I/R group, Oxy pretreatment attenuated skeletal muscle damage, decreased serum TNF-α levels, and inhibited the expression levels of TLR4/NF-κB in the gastrocnemius muscle. Furthermore, Oxy treatment significantly increased serum ATP levels and the contractility of the skeletal muscles. SIRT1 and PGC-1α levels were significantly reduced in gastrocnemius muscle after I/R. Oxy pretreatment recovered these protein expression levels. Conclusion. Tourniquet-induced acute limb I/R results in morphological and functional impairment in skeletal muscle. Pretreatment with Oxy attenuates skeletal muscle from acute I/R injury through inhibition of TLR4/NF-κB-dependent inflammatory response and protects SIRT1/PGC-1α-dependent mitochondrial function.